Application of ATR-FTIR spectroscopy for profiling of non-structural carbohydrates in onion (Allium cepa L.) bulbs. (30th October 2021) - Krähmer, Andrea; Böttcher, Christoph; Gudi, Gennadi; Stürtz, Melanie; Schulz, Hartwig
Graphical abstract: Abstract: Qualitative and quantitative composition of non-structural carbohydrates comprising glucose, fructose, sucrose and fructooligosaccharides (FOS) is one of the key determinants of market suitability, storability and technological processability of onions. To develop a cost-effective and rapid tool for carbohydrate profiling, applicability of attenuated total reflectance Fourier-transform infrared (ATR-FTIR) spectroscopy of onion juice was investigated with special regard to FOS patterns. As reference, detailed carbohydrate profiles of onion juices were generated by high-performance liquid chromatography coupled with evaporative light scattering detection (HPLC-ELSD). Hierarchical cluster analysis (HCA) of ATR-FTIR spectra was successfully applied for classifying onions into fresh market, storage and dehydrator type according to HPLC-ELSD profiles. A bootstrapping method for automatized test-set validation by projection to latent structures (PLS) algorithms using HPLC and ATR-FTIR spectroscopy data was developed. Model statistics showed promising perspectives for reliable quantification of individual saccharides and sum parameters. The presented methodology allows estimating the nutritional and pre-biotic value directly during cultivation and processing.